Effect of Precursor and Temperature Annealing on the Catalytic Activity of Intermetallic Ni3Sn2 Alloy - Rodiansono Rodiansono; Atina Sabila Azzahra; Sadang Husain; Pathur Razi Ansyah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
The effect of nickel precursors and the temperature annealing to obtain intermetallic Ni3Sn2 alloy catalysts on its activity and selectivity in the selective hydrogenation of biomass-derived furfural (FFald) were investigated. Two types of nickel precursors (c.a., i) nickel metal (Ni°) derived from Raney®nickel and ii) nickel ion (Ni2+) derived from nickel chloride) were employed as the starting materials via hydrothermal at 423 K for 24 h followed by reduction with H2 at the elevated temperature of 573-873 K for 1.5 h. The physico-chemical properties of the intermetallic Ni3Sn2 were characterized by XRD, N2-, and H2-adsorption, ICP-AES, and NH3-TPD. The intermetallic Ni3Sn2 alloy catalysts, both bulk and supported, demonstrated high activity and selectivity towards hydrogenation of FFald. The activity and selectivity of g-Al2O3 and AA-supported Ni3Sn2 alloy catalysts in the hydrogenation of FFald to furfuryl alcohol (FFalc) were maintained even after annealing at up to 873 K, but that of bulk Ni3Sn2 drastically dropped. Ni-Sn alloy catalysts which were obtained from Raney®Ni precursor showed more stable than that of nickel salts during hydrogenation of furfural to furfuryl alcohol. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).